Carboxymethylation of (1 → 6)-β-glucan (lasiodiplodan): Preparation, characterization and antioxidant evaluation. (20th August 2015) - Kagimura, Francini Y.; da Cunha, Mário Antônio A.; Theis, Thais V.; Malfatti, Carlos R.M.; Dekker, Robert F.H.; Barbosa, Aneli M.; Teixeira, Sirlei D.; Salomé, Kahlil
Highlights: Carboxymethylation, characterization and antioxidant activity of LAS are described. Native and carboxymethylated lasiodiplodan presents high thermal stability. Carboxymethylation improved the polysaccharide's water solubility. Carboxymethylation improved the polysaccharide's antioxidant capacity. Abstract: d -Glucans possess immunomodulatory activities and potential for the development of new therapeutic agents. Biological activities can be enhanced in these biopolymers through chemical derivatization, e.g., carboxymethylation. This work presents the carboxymethylation, characterization and the evaluation of antioxidant activities of the exocellular (1 →  6)-β-d -glucan produced by Lasiodiplodia theobromae MMPI. Thermal analysis indicated that the native and carboxymethylated polysaccharides presented four stages of mass-loss. The first stage occurred at 125 °C (loss of water) with two consecutive events of mass loss (200–400 °C) attributed to polymer degradation and the fourth stage between 425 and 620 °C (final decomposition). Scanning electron microscopy analysis indicated that the gross morphological features of lasiodiplodan were ruptured following carboxymethylation. X-ray diffractometry analysis demonstrated that the native and carboxymethylated polysaccharides presented a non-crystalline structure. Carboxymethylation contributed to improving the polysaccharide's water solubility and antioxidant capacity.